2022
DOI: 10.3390/vaccines10050719
|View full text |Cite
|
Sign up to set email alerts
|

Using Integrative Behavior Model to Predict COVID-19 Vaccination Intention among Health Care Workers in Indonesia: A Nationwide Survey

Abstract: Background: Health care workers (HCWs) are a high-priority group for COVID-19 vaccination for several reasons. Health behavior theory-based studies on the intention or acceptability of COVID-19 vaccination among Indonesian HCWs is lacking. Using an integrated behavioral model, this research sought to identify Indonesian health care workers’ intentions to obtain COVID-19 vaccines. Methods: A countrywide cross-sectional questionnaire-based survey was conducted. The questionnaire was constructed on the basis of I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 36 publications
2
16
1
Order By: Relevance
“…Moreover, the model with added demographic variables showed a 54.1% variance in vaccination intention ( R 2 = 0.541). This number is higher than our previous study on Indonesian health workers, which used the same method ( R 2 = 0.42) [ 12 ]. This finding is also comparable to previous studies on the general population, which integrate health behavior theories to predict COVID-19 vaccine acceptance [ 13 ].…”
Section: Discussioncontrasting
confidence: 57%
“…Moreover, the model with added demographic variables showed a 54.1% variance in vaccination intention ( R 2 = 0.541). This number is higher than our previous study on Indonesian health workers, which used the same method ( R 2 = 0.42) [ 12 ]. This finding is also comparable to previous studies on the general population, which integrate health behavior theories to predict COVID-19 vaccine acceptance [ 13 ].…”
Section: Discussioncontrasting
confidence: 57%
“…Efforts to minimize the incidence and severity of COVID-19 are mainly through vaccination due to the lack of an effective curative treatment [ 5 , 6 ]. Despite the remarkable production of vaccines and unprecedented heights reached in research and manufacturing speed, the worldwide threat of this virus is far from ending, especially for high-risk groups.…”
Section: Introductionmentioning
confidence: 99%
“…The integrated behavior model (IBM) is a framework for understanding and influencing human behavior centered on intention [ 18 ]. Theoretical behavior models have been widely used to determine the intention of COVID-19 vaccination in the general population, medical and nursing students, and healthcare workers [ 5 , 17 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The study found high booster vaccination acceptance among HCWs in Jakarta, with 89.3% agreeing to take the vaccine. This number is higher than a previous study among HCWs analyzing the intention to get the primary shots, which reported that only 61.3% of participants were willing to get the vaccine [ 7 ]. After the previous study, more evidence of the COVID-19 vaccine being safe and effective was released, and hesitancy has been known to be a matter of time and context [ 15 ].…”
Section: Discussionmentioning
confidence: 71%
“…The most critical public health approach for controlling the pandemic is to achieve very high vaccination coverage for primary and booster doses. The nationwide research of HCWs during the initial distribution revealed that hesitation persists among HCWs [ 7 ]. Understanding the motives and challenges impacting the acceptance of the booster vaccination is critical.…”
Section: Introductionmentioning
confidence: 99%